Efektivitas Asistensi Mengajar Dalam Menigkatkan Kualitas Dalam Pembelajaran Di SDN 1 Aikmel Utara - Hamdi, Zulfadli; Apriandi, Muhammad Mirwan; Rizaldo, Enki; Anggraini, Sapma Dewi; Suriani, Lilik; Apriantari, Baiq Risa; Astuti, Maeli (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Teaching assistance is a strategic program to enhance the effectiveness of the learning process through in-class support. This study aims to analyze the role of teaching assistants, their impact on student learning, and the challenges faced in the implementation of the program at SDN 1 Aikmel Utara. The research uses a qualitative descriptive method with a case study approach, involving teachers, teaching assistants, and students as the main informants. Data collection techniques include direct observation, semi-structured interviews, and document analysis. The research results show that teaching assistants play a significant role in supporting classroom management, guiding students who need additional help, and creating an interactive learning atmosphere